PENGEMBANGAN MEDIA PEMBELAJARAN SEJARAH LOKAL BERBASIS AUDIO VISUAL CORAK KAIN SASIRANGAN DI SMAN 5 BANJARMASIN - Fitri Mardiani (Universitas Negeri Yogyakarta, 2018)
Local history includes a wide range of knowledge and noble values in a society that can be used as one perspective that is held in life. Those values can be attributed to learning course that leads to the affective attitude of the students. For society, the fabric sasirangan open just an ordinary cloth but the terms of the meaning and significance of the sublime. In this study local history lesson on the meaning attributed to shades of fabric sasirangan. The method used in this research is descriptive evaluative namely by combining the results of field exposure and testing of the products with evaluative methods. Stages in the development of this research are: 1) The preliminary research stage, 2) stage of media development, 3) stages try uj media (product). For data analysis hit feasibility media has been developed using a Likert scale ranges 5. The media effectiveness test using the test T. From the T test results we can conclude that H0 is rejected. Then there are differences in effect on student achievement scores between the experimental class and control class. Through these results we can conclude that the use of instructional media berbasi sasirangan fabric patterns can impact the value of student achievement. As for the assessment of cultural awareness, It can be said there has been a good improvement of student achievement scores between before being given to the media after being given media.